Prosedur dalam Menganalisis Butir Soal di Madrasah Ibtidaiyah - Ina Magdalena; Anggit DW Cahyani; Friska Auliani Wijaya; Marni Marni; Alyarizqi Nafidhia T. (Jurnal Halaqah, 2020)
As educators it is supposed to make questions for students in school. This problem can see the extent to which students are able to master the material and see how students' ability to absorb material that has been taught by the teacher. Then the problem is analyzed based on the existing provisions. At this time there are still prospective educators who feel confused about how to analyze each item. With this, a study was conducted at MI Darul Hidayah to see how the teacher analyzed the items. Based on the results of the study, it was found that there were several stages when analyzed and when the analysis was not only done in one trial but there were other stages.